Size and morphology-controlled synthesis of mesoporous hydroxyapatite nanocrystals by microwave-assisted hydrothermal method. Issue 10 (July 2018) - Kumar, Govindan Suresh; Karunakaran, Gopalu; Girija, Easwaradas Kreedapathy; Kolesnikov, Evgeny; Minh, Nguyen Van; Gorshenkov, Mikhail V.; Kuznetsov, Denis
Abstract: We report the rapid microwave-assisted hydrothermal synthesis of mesoporous hydroxyapatite (HAp) nanocrystals with controlled size, morphology, and surface area using various organic modifiers as regulators. The products were analyzed for their crystalline nature, phase purity, morphology, particle size and pore size distribution. Results indicated that ascorbic acid, cetyltrimethyl ammonium bromide (CTAB) and polyvinylpyrrolidone (PVP) play an important role to obtain needle like, rod like and fiber like mesoporous HAp nanocrystals with different specific surface area by controlling growth habit of HAp along c -axis. In addition, the prepared samples were B-type carbonated HAp similar to bone minerals. Therefore, the present approach can be a promising way to obtain precursor for making tissue engineering scaffolds, drug/protein delivery carriers and bone fillers with tunable characteristics.